1967
DOI: 10.1111/j.1432-1033.1967.tb19522.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Free Amino Groups in the Blood Group Activity of M and N Mucoids

Abstract: 1. The M and N blood group substances were treated with different amino-group reagents, such as : acetic-, succinic-, and phthalic-anhydrides, benzyloxycarbonylchloride, dinitrofluorobenzene, nitrous acid and 0-methyl-isourea.2. It was shown that these reagents blocked or destroyed 2-4 free amino groups (mainly lysine E-NH, groups) per one subunit of M or N blood group substance of mol. wt. 30,000. No other effects were found under the conditions used.3. The blocking or decomposition of amino groups, connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

1969
1969
1995
1995

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 12 publications
4
16
0
1
Order By: Relevance
“…The measurements of absorbance at 420 nm after modification with 2-methoxy-5-nitrotropone revealed that 9-11 nitrotroponyl microequivalents were introduced to 100mg of the glycoprotein. These values were in accord with our previous data [13]. The release of reversibly blocking residues was achieved in 50-70% of the total number of modified amino groups.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The measurements of absorbance at 420 nm after modification with 2-methoxy-5-nitrotropone revealed that 9-11 nitrotroponyl microequivalents were introduced to 100mg of the glycoprotein. These values were in accord with our previous data [13]. The release of reversibly blocking residues was achieved in 50-70% of the total number of modified amino groups.…”
Section: Resultssupporting
confidence: 82%
“…The small amount of specific receptors among many unspecific oligosaccharide chains could justify the fact that no conclusive chemical evidence for the difference in structure of oligosaccharides of M and N glycoproteins has been reported so far. We found [13] that modification of amino groups of the glycoproteins abolished their capacity to inhibit rabbit anti-M and anti-N sera, and this finding was confirmed later by Ebert et ul. [4].…”
supporting
confidence: 78%
“…The reactivity with rabbit immune sera was found to be dependent on the presence of free amino groups of lysine residues, but the reactivity with phytoagglutin i n s from V . graminea was not affected by the modification of amino groups [20]. Although lysine was found in peptides liberated during the alkaline degradation the loss of both activities suggested the participation of the described trisaccharide and disaccharide structures in the reaction with rabbit sera and phytoagglutinins, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Determination of the blood group activity with rabbit immune sera and anti-N phytoagglutinins from Vicia gramineu was described earlier [20]. The inhibition of viral hemagglutination was estimated by the method of Tamm and Horsfall [21], influenza virus A, was obtained from the Dept.…”
Section: Other Methodsmentioning
confidence: 99%
“…Arabitol was used as internal standard. The chromatographic separation was performed with the liquid phase methylphenylsilicone (OV 17) 20/, (w/w) on Chromosorb G. Temperature ("c) phate buffer, p H 7, according to Lisowska and Morawiecki [8], modified by Merz and Roelcke [9]. Electrophoresis on cellulose acetate strips was carried out in sodium veronal buffer, pH 8.6, 25 min a t 250 V, 5 mA.…”
Section: Methodsmentioning
confidence: 99%